Der österreichische Protestantismus im Spiegel seiner Rechtsgeschichte - Schwarz, Karl (Jus Ecclesiasticum, 2017)
Karl W. Schwarz takes up the legal history of Austrian Protestantism and spans an arc from the sixteenth century, covering the epoch of secret protestantism to the tolerance and emancipation of the Acatholics in the nineteenth century, as well as the Catholic corporative state era, the Nazi period, and the Second Republic.